Identifying barriers towards a post-growth economy: A political economy view - Sebastian Strunz; Harry Schindler (Helmholtz-Zentrum für Umweltforschung (UFZ), 2017)
In this paper, we take a political economy perspective on barriers that inhibit a transition beyond the growth-paradigm - that is, we frame transition barriers as looming distributional conflicts. Within the current paradigm, distributional conflicts are mitigated via economic growth. Hence, the solution of these distributional conflicts is a prerequisite for a successful transition. Specifically, we analyze three examples of transition barriers. First, unemployment represents the most commonly cited reason why economic growth is considered indispensable. Second, pension schemes rely on economic growth to offset demographic change. Third, alternative indicators to Gross Domestic Product (GDP) have not succeeded in replacing GDP as a standard metric of economic welfare. In each of these three examples, we identify actor-interest constellations that foster the status quo. We conclude that compensating those actors who would presumably be worse off due to a transition beyond the growth paradigm may be inevitable to mitigate and overcome the distributional effects to be triggered by the transition.
Keywords: 330